THE INFLUENCE OF ATMOSPHERE, PRICE, AND PRODUCT QUALITY ON GELATO PURCHASE DECISIONS THROUGH BRAND IMAGE - Muhammad Shofwan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study analyzes the effects of product quality, price, and store atmosphere on brand image and the subsequent effect of brand image on the purchase decisions of Gelato X consumers. The research was conducted at a gelato outlet in the Blok M area from August to December 2025. Primary data were collected through questionnaires distributed to consumers who had purchased Gelato X products, while secondary data were obtained from relevant articles and scientific journals. Purposive sampling produced 112 valid respondents. The data were analyzed using Partial Least Squares Structural Equation Modeling. Product quality had a positive and significant effect on brand image (coefficient 0.314; p = 0.005). Price also had a positive and significant effect on brand image (coefficient 0.327; p = 0.001), as did store atmosphere (coefficient 0.303; p = 0.021). Brand image had the strongest positive effect on purchase decisions (coefficient 0.791; p < 0.001). Product quality, price, and atmosphere explained 75.1% of the variance in brand image, while brand image explained 62.6% of purchase decisions. The findings emphasize consistent product quality, value-based pricing and promotions, and a comfortable store environment as the basis for strengthening the brand and increasing purchases.